Terapia de fotobiomodulação e campo magnético estático no alívio da dor associada à epicondilite lateral: ensaio clínico randomizado, placebo controlado e triplo-cego - Oliveira, Marcelo Ferreira Duarte de (2021)
Lateral epicondylitis (EL) is one of the most frequently encountered lesions in the upper extremity and is the most common cause of adult elbow pain known as tennis elbow. This clinical condition has a significant impact on the health sector and society at large. Treatment options include therapeutic exercises, orthotics, shock waves or ultrasound, in addition to corticosteroid injections. The photobiomodulation therapy (PBMT) has been presenting satisfactory results in the stimulation of tendon healing, obtaining favorable results in the tendon repair process. PBMT can be used as a therapeutic tool for the management of epicondylitis, however, further investigations are necessary to establish the optimal parameters of use. Therefore, the purpose of this study was to investigate the efficacy of two different PBMT devices (MR5TM Active Pro and LEAP SportsPodTM) in relieving pain and associated sensitivity in patients with lateral epicondylitis. To this end, a randomized, placebo controlled, triple blind trial was conducted, for which 75 adults of both genders was randomly assigned to three experimental groups. Individuals received photobiomodulation therapy at 4 points of the epicondyle region. Thirty days after treatment with phototherapy participants was evaluated with the degree of pain classification (visual analogue scale VAS), grip strength evaluation, in addition to satisfaction with the overall result of the study. There was a decrease in the level of pain in more than 30% of the group treated with the MR5® Active Pro device compared to placebo.TFBM with LEAP SportsPodTM (IR Pad) and TFBM/CM with MR5TM Active Pro (Activ Pro) were effective in relieving pain and tenderness in patients with lateral epicondylitis. However, no differences were observed regarding the effectiveness of the therapies to assess the grip strength of these patients.